Odpowiedź:
a)
2ˣ⁻⁴×8³⁻²ˣ = 4³ˣ⁻³
2ˣ⁻⁴×2³⁽³⁻²ˣ⁾ = 2²⁽³ˣ⁻³⁾
2ˣ⁻⁴×2⁹⁻⁶ˣ= 2⁶ˣ⁻⁶
2ˣ⁻⁴⁺⁹⁻⁶ˣ = 2⁶ˣ⁻⁶
2⁵⁻⁵ˣ = 2⁶ˣ⁻⁶ ⇔ 5-5x=6x-6 ⇒ -5x-6x = -6-5⇒ -11x = -11 /÷(-11) ⇒ x = 1
spr.
2¹⁻⁴×8³⁻² = 4³⁻³
2⁻³×8¹ = 4⁰
1/8×8 = 1
1=1
L=P
b)
5ˣ²⁻⁴ˣ⁻⁵ = 1
5ˣ²⁻⁴ˣ⁻⁵ = 5⁰ ⇔ x²-4x-5=0
x²-4x-5=0
a=1, b= -4, c= -5
Δ=(-4)² - 4×1×(-5) = 16+20 = 36
√Δ =√36 = 6
x₁ =(4-6)/2 = (-2)/2 = -1 ∨ x₂ =(4+6)/2 = 10/2 = 5
spr.
dla x= -1 dla x =5
5⁽⁻¹⁾²⁺⁴⁻⁵ = 1 5²⁵⁻²⁰⁻⁵ = 1
5¹⁺⁴⁻⁵=1 5²⁵⁻²⁵ = 1
5⁰ = 1 5⁰ = 1
1=1 1=1
L=P L=P
Szczegółowe wyjaśnienie: